Manajemen supervisi kepala sekolah dalam rangka meningkatkan mutu mengajar guru di SD Muhammadiyah Suronatan Kota Yogyakarta - Sri Eni Utaminingsih; Mundilarno Mundilarno (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
This study aims to describe management include planning, organizing, evolution and follow up of the supervision conducted by the principal Suronatan Muhammadiyah schools and to determine the factors that support and hinder the implementation of the supervision conducted by the Elementary School Principal Suronatan Muhammadiyah Yogyakarta. This research was a qualitative model. The data collection was part of the process of searching for data and the part of the data analysis process. This means that, at the time of collecting data, the researcher processed analysis, i.e. reduce, categorize into the group of data, ranging present, and draw conclusions. The results showed that the principal has been carrying out supervision of management include planning, organizing, evaluation, and follow up of the supervision carried principally at SD Muhammadiyah Yogyakarta Suronatan. Planning, principals can manage the environment becomes active and creative in improving the quality of learning. Organizing shows how the principal resource organizes, exiting resource in the school to active the highest effectiveness. Evaluation and follow on supervision of principal conducted to determine the factors that support and hinder the implementation of supervision. Another factor that supports the competence Management Support; Empowerment strategies; Supervision Department; presence of Classroom Action Research (classroom Action Research / CAR); Principal Supervision Strategy development; Principals and teachers are professional, innovative, and creative, Among another factor that hinder no indicators of learning materials, the use of which has not varied teaching methods, and lack of control of teachers in active learning models and there is no supervision program is thorough and systematic.